1999
DOI: 10.1007/s004210050554
|View full text |Cite
|
Sign up to set email alerts
|

Role of xanthine oxidase in delayed lipid peroxidation in rat liver induced by acute exhausting exercise

Abstract: The aim of this study was to examine whether xanthine oxidase (XOD)-derived hepatic oxidative damage occurs in the main not during but following strenuous exercise. The degree of damage to hepatic tissue catalyzed by XOD was investigated immediately and 3 h after a single bout of exhausting exercise, in allopurinol and saline injected female Wistar rats. Allopurinol treatment resulted in increased hypoxanthine and decreased uric acid contents in the liver compared with the saline treated group, immediately and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1
6

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
4
26
1
6
Order By: Relevance
“…Some studies reported the upregulation of variables of increased generation of reactive oxygen species such as lipid peroxidation, accumulation of nuclear 8-hydroxydeoxyguanosine, and induction of heat-shock proteins in the liver after acute exercise [32,44]. Here, we studied the effect of a diet enriched with vitamin C and vitamin E for 4 weeks before the single exercise bout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported the upregulation of variables of increased generation of reactive oxygen species such as lipid peroxidation, accumulation of nuclear 8-hydroxydeoxyguanosine, and induction of heat-shock proteins in the liver after acute exercise [32,44]. Here, we studied the effect of a diet enriched with vitamin C and vitamin E for 4 weeks before the single exercise bout.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not attempt to measure any biomarkers of oxidative stress, the increase in antioxidative gene expression found in the whole-genome-expression analysis (data not shown) suggests that our exercise protocol could have induced oxidative stress in the liver. Moreover, increased generation of reactive oxygen species in the liver of rats after acute exercise has been reported [32,33]. Therefore, we evaluated the effect of an antioxidant-rich diet on the effects of the single bout of exercise.…”
Section: Microarray Expression Analysismentioning
confidence: 99%
“…Η προκαλούμενη από την άσκηση αύξηση της συγκέντρωσης της MDA στο πλάσμα μετριάστηκε και μετά από στοματική χορήγηση αλοπουρινόλης σε δόση των 300 mg σε αθλητές 2 h πριν από μαραθώνιο . Ο αντιοξειδωτικός ρόλος της αλοπουρινόλης επιβεβαιώθηκε και σε ακόμα μία εργασία καθώς η ενδοπεριτοναϊκή χορήγησή της σε επίμυες σε δόση 44 mg/kg σωματικού βάρους δεν επέτρεψε να αυξηθεί η συγκέντρωση των TBARS στο ήπαρ 3 h μετά από τρέξιμο μέχρι εξάντλησης σε δαπεδοεργόμετρο (Koyama et al, 1999). Προς την ίδια κατεύθυνση ήταν και τα αποτελέσματα μίας εργασίας, στην οποία χορηγήθηκε αλοπουρινόλη από το στόμα σε δόση 30 mg/kg σωματικού βάρους και ενδοπεριτοναϊκά σε δόση 5 mg/kg σωματικού βάρους σε άλογα, 12 και 2 h πριν την εφαρμογή του πειραματικού πρωτοκόλου (Mills et al, 1997).…”
Section: οξειδοαναγωγάση της ξανθίνηςunclassified
“…Από τα παραπάνω είναι φανερό ότι η αλοπουρινόλη είχε αντιοξειδωτικό ρόλο στις λίγες σχετικές εργασίες της βιβλιογραφίας, καθώς μετρίασε την οξειδωτική δράση της άσκησης σε πειράματα τόσο στον άνθρωπο όσο και σε πειραματόζωα. Σε ορισμένες από τις προαναφερθείσες εργασίες και σε κάποιες ακόμα εξετάστηκε και η επίδραση της χορήγησης της αλοπουρινόλης στην απόδοση τόσο των ανθρώπων όσο και των πειραματόζωων, που χρησιμοποιήθηκαν (Gomez-Cabrera et al, 2003, 2006Koyama et al, 1999;Gavin & Struthers, 2005;Sutton et al, 1980). Ωστόσο, σε καμία από αυτές δε βρέθηκε επίδραση, όπως μετρήθηκε από το χρόνο που απαιτείται για να επέρθει η εξάντληση.…”
Section: υποξανθίνηunclassified
See 1 more Smart Citation